Pemberdayaan masyarakat Gampong Baro, Aceh Besar dalam upaya mitigasi bencana geologi - Muhammad Ridha Adhari; Dewi Sartika; Dina Gunarsih; Hidayat Syah Putra; Rifqan Rifqan; Gartika Setiya Nugraha; Akmal Muhni (Universitas Syiah Kuala, 2025)
Gampong Baro, subdistrict of Mesjid Raya, Aceh Besar was strongly hit by the Indian ocean earthquake and tsunami in 2004. This is mainly due to its location which is situated near the shoreline. Moreover, many villagers of the Gampong Baro lost their lives during that geological hazard. It is well known that earthquake and tsunami may potentially return again in the future, and may cause another great misery. Our earlier, current study shows that many villagers of Gampong Baro are not familiar with the earthquake and tsunami hazards, and they have very little understanding of these geological phenomenon. Therefore, in order to help mitigate this geological hazard, we decided to organize a training about geological hazards mitigation procedures for the villagers of Gampong Baro, Aceh Besar. There are two objectives of this community service, which are: (1) to improve geological knowledge of the villagers of Gampong Baro, Aceh Besar; and (2) to conduct training about geological hazards mitigation procedures. Qualitative analysis, including focus group discussion, interviews, questionnaire, and surveys was carried out during this activity. Our findings show that villagers of Gampong Baro, Aceh Besar are eager to learn about geological knowledge, and have strong commitment to better understand many geological hazard mitigation procedures. They were very happy that we provided this training because they considered it as an important training, considering the potential of many geological hazards that may hit their village.